Panel data analysis on corporate effective tax rates of some listed large firms in Nigeria - Samuel Olorunfemi Adams; Philomena Omoshade Balogun (Dutch Journal of Finance and Management, 2020)
Corporate effective tax rates (ETR) of large Nigerian listed firms during the new tax regime as well as the influence of firm size, leverage, return on asset, capital intensity, and inventory intensity on corporate effective tax rate was investigated. The study aims to examine the influence of some corporate tax attributes in some selected large public listed firms within and across Nigeria with avoidance of corporate effective tax rates (ETR). The data used in the study was extracted from the 2019 Nigeria Annual Financial reports. The data were collected from the period 2012 to 2018, the period where Nigeria imposed a new tax regime on the current year assessment system (effective from the year 2012). Pooled ordinary least square (POLS), fixed effect and random effect regression were applied to the data, findings from the study revealed that the random effect regression model was preferred for result interpretation. It was also discovered that; firm size (FSIZE), return on assets (ROA), and inventory intensity (INVINT) have a positive and significant influence on corporate effective tax rates (ETR) avoidance. Firm leverage (LEV) and capital intensity (CAPINT) on the other hand has an insignificant inverse influence on effective tax rates (ETR). Hence, this study suggested that firm size (FSIZE), return on assets (ROA), and inventory intensity (INVINT) is the major variable that positively influences the corporate effective tax rates (ETR) the listed large firms in Nigeria.
Keywords: 650; effective tax rates; return on asset; firm leverage; firm size; capital intensity; inventory intensity